2016
DOI: 10.1111/anti.12302
|View full text |Cite
|
Sign up to set email alerts
|

The Suburb as a Space of Capital Accumulation: The Development of New Towns in Shanghai, China

Abstract: Drawing attention to the governing role of capital accumulation and its interaction with the state, this study examines the dynamics of the new wave of suburbanization in China, which is characterized by the development of new towns. New towns essentially function as a spatial fix in China's contemporary accumulation regime. Rather than resulting from capital switching from the primary to the secondary circuits, new towns help to collect funds for the leverage of industrial capital and thus simultaneously sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 37 publications
1
89
0
5
Order By: Relevance
“…First and foremost, as shown in the studies of university towns (Sum, 2018) and new towns (Shen and Wu, 2017), they are mega urban projects created by planning centrality, because they are not only master-planned but are also produced by planning policies. The policy of land development quotas leads to land consolidation in suburban areas (Tian et al, 2017).…”
Section: Governing Suburban Mega Urban Projectsmentioning
confidence: 99%
“…First and foremost, as shown in the studies of university towns (Sum, 2018) and new towns (Shen and Wu, 2017), they are mega urban projects created by planning centrality, because they are not only master-planned but are also produced by planning policies. The policy of land development quotas leads to land consolidation in suburban areas (Tian et al, 2017).…”
Section: Governing Suburban Mega Urban Projectsmentioning
confidence: 99%
“…The suburban district of Songjiang, for example, has seen massive residential development, as well the development of a university town and industrial parks (Shen and Wu, 2012). Subsequently, the core city areas have been upgraded for office and commercial use, while the suburbs have been industrialized to accommodate new global-oriented manufacturing industries (Shen and Wu, 2016). The division of economic functions between the central city and suburban districts has thus led to the creation of a more metropolitan scale of development, and in essence this is the scale of the city-region.…”
Section: Periodization Of Chinese State Spatial Selectivitymentioning
confidence: 99%
“…Whilst the dominant discourse on mega projects is mostly based on empirical studies from the global North, mega projects have also proliferated in Asian countries (Shatkin ; Sonn et al ) whereby China has emerged as a hotbed for large‐scale urban projects (Jiang et al ; Li and Chiu ; Shen and Wu ; Wu and Waley ). However, increasingly more studies express doubt that the concept of neoliberalisation is suited to explain the Chinese urban development process (Wu ; Wu and Phelps ).…”
Section: The Social Impact Of Mega Urban Projectsmentioning
confidence: 99%
“…The purpose of this paper is to explore the problem of in‐situ marginalisation as a major social impact of Chinese mega projects and its underlying causes. Our paper draws on the findings from Lingang new town, which is part of a growing number of peri‐urban mega projects that have been developed in recent decades (Hsing ; Shen and Wu ; Wu and Phelps ). We contend that the theoretical framework of neoliberalisation whereby mega projects mainly serve to garner financial profits through land revalorisation (Brenner and Theodore ; Swyngedouw et al ; Tarazona Vento ) cannot explain the social problems found in Lingang.…”
Section: Introductionmentioning
confidence: 99%